RECONSTRUCTION OF ECONOMIC RESOURCES IN THE TOURISM INDUSTRY - Городянська, Лариса В. (Journal of Strategic Economic Research, 2023)
This industry as an economic and technological system for forming and delivering tourism products is based on certain economic resources, whose reconstruction has not been sufficiently studied. Therefore, the purpose of the paper is to determine the composition of economic resources of the tourism industry and explore directions of their reconstruction in modern conditions. To fulfill the tasks and achieve the goal of the research, the following method was used: the analysis of literary sources for the preparation of the theoretical basis of the study, the dialectical method for structuring the tourism industry, the method of decomposition, systematic analysis and synthesis for the study of the types and directions of reconstruction of resources in tourism industry, the method of theoretical generalizations when forming current and final conclusions. The structure of the tourism industry organization has been formed, which covers four stages: production of tourism services, assembly, sale, and consumption of a tourism product or service. Financial and economic processes at these stages of the organization of the tourism industry are focused on the transformation of economic resources into tourism product in the process of circulation of intellectual capital. It has been established that the tourism industry economic resources capable of reconstruction are the intellectual potential labor resources and means of work, which together with financial resources, entrepreneurship and information resources form the resource support of the tourism industry and create a basis for developing and updating the tourism product. For the first time, the concept of resource reconstruction in the tourism industry is introduced, the types of economic resources of the tourism industry are defined and justified, and the components of resource provision of the tourism industry are investigated. It is justified that the most important aspects of ensuring the reconstruction of economic resources are financial stability, infrastructure, labor market, marketing, technological innovation, sustainability and conservation of resources. It is argued that effective use of economic opportunities for ensuring resource reconstruction processes serve as a kind of investment in tourism infrastructure development, technological innovations and, in general, key factors for long-term success in the tourism industry.